2019
DOI: 10.3390/w11020300
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Joint Return Period for Connected Edge Data

Abstract: For better displaying the statistical properties of measured data, it is particularly important to select a suitable multivariate joint distribution model in ocean engineering. According to the characteristics and properties of Copula functions and the correlation analysis of measured data, the nonlinear relationship between random variables can be captured. Additionally, the models based on the Copula theory have more general applicability. A series of correlation measure index, derived from Copula functions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Extreme phenomena affecting Mexico, such as the occurrence of two hurricanes at the same time (Ingrid and Manuel in 2013), should be studied with mixed probability distributions of two or more populations [53]. Recent studies have shown that when using mixed distributions, such as Mixed Gumbel, Gumbel-Logistic and Gumbel-Hougaard Copula, the main problem is the adaptation of extreme values [54].…”
Section: Discussionmentioning
confidence: 99%
“…Extreme phenomena affecting Mexico, such as the occurrence of two hurricanes at the same time (Ingrid and Manuel in 2013), should be studied with mixed probability distributions of two or more populations [53]. Recent studies have shown that when using mixed distributions, such as Mixed Gumbel, Gumbel-Logistic and Gumbel-Hougaard Copula, the main problem is the adaptation of extreme values [54].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [61] proposed an adaptive parameter optimized VMD. The other signal decomposition methods have also been proposed in recent years [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76].…”
Section: Vmdmentioning
confidence: 99%
“…It plays the role of supporting the main shaft and transmitting torque. Its operating state directly affects the working state of the motor [1][2][3][4][5]. According to statistics, when a rotating machine occurs fails, more than 30% of the faults are caused by bearings [6][7][8].…”
Section: Introductionmentioning
confidence: 99%